PAT: a comprehensive database of prokaryotic antimicrobial toxins. Issue Volume 51:Issue D1(2023) (16th October 2022) - Liu, Ya; Liu, Sheng; Pan, Zhuo; Ren, Yu; Jiang, Yiru; Wang, Feng; Li, Dan-dan; Li, Yue-zhong; Zhang, Zheng
Abstract: Antimicrobial toxins help prokaryotes win competitive advantages in intraspecific or interspecific conflicts and are also a critical factor affecting the pathogenicity of many pathogens that threaten human health. Although many studies have revealed that antagonism based on antimicrobial toxins plays a central role in prokaryotic life, a database on antimicrobial toxins remains lacking. Here, we present the prokaryotic antimicrobial toxin database (PAT, http://bioinfo.qd.sdu.edu.cn/PAT/ ), a comprehensive data resource collection on experimentally validated antimicrobial toxins. PAT has organized information, derived from the reported literature, on antimicrobial toxins, as well as the corresponding immunity proteins, delivery mechanisms, toxin activities, structural characteristics, sequences, etc. Moreover, we also predict potential antimicrobial toxins in prokaryotic reference genomes and show the taxonomic information and environmental distribution of typical antimicrobial toxins. These details have been fully incorporated into the PAT database, where users can browse, search, download, analyse and view informative statistics and detailed information. PAT resources have already been used in our prediction and identification of prokaryotic antimicrobial toxins and may contribute to promoting the efficient investigation of antimicrobial toxin functions, the discovery of novel antimicrobial toxins, and an improved understanding of the biological roles and significance of these toxins.